Variations in packed red cell volume and trypanosome prevalence and relationships with reproductive traits in East African Zebu cows exposed to drug-resistant trypanosomes - Rowlands, G.J.; Woudyalew Mulatu; Nagda, S.M.; D'Ieteren, G.D.M. (Elsevier, 1995)
Approximately 320 East African Zebu cows over 36 months of age were monitored monthly from 1986 to 1992 in nine village herds in an area of high trypanosomiasis risk in southwest Ethiopia where there was resistance to all available trypanocidal drugs. Cows were individually treated with diminazene aceturate, either when they were detected parasitaemic and their packed red cell volume (PCV) decreased below 26 percent or when they showed clinical signs of trypanosomiasis. The average annual monthly trypanosome prevalence was 24 percent and the number of treatments of diminazene aceturate per cow per year was 3.1 both of which increased with age. Mean PCV decreased and mean trypanosome prevalence increased during lactation. There was a significant linear association between the time detected parasitaemic during lactation and calving interval. When corrected for frequency of parasitaemia and treatment there was also an average reduction of 8.4 + 2.6 days in calving interval per percent unit increase in PCAge at first calving decreased by 0.44 + 0.26 months per percent unit increase in mean PCV maintained between 24 and 30 months corrected for parasitaemia and treatment. The percentage of pregnancies terminating in abortions significantly increased from 6.8 + 1.0 percent to 10.4 + 1.3 percent when cows detected parasitaemic at least once during the last three months of pregnancy were compared with cows not detected parasitaemic at least once during the last three months of pregnancy were compared with cows not detected parasitaemic. The largest increase to 19.4 +- 4.3 percent was in cows with low mean PCVs < 22 percent. It was concluded that cows which were able to maintain higher than average PCVs when parasitaemic showed superior reproductive performance than those with lower than average PCVs.